PENGARUH INFLASI INDONESIA TERHADAP PENERIMAAN PENANAMAN MODAL ASING LANGSUNG KOREA SELATAN DI INDONESIA PERIODE 2000-2014 - Sugiartiningsih Sugiartiningsih (Universitas Kristen Maranatha, 2017)
One of the keys to success in improving the economic prosperity of a country is evident from its response to bilateral or multilateral relations, particularly in the making of investments. Indonesia as a country that has started the construction of the New Order can not be separated from the role of foreign capital. In reality in the 1990s looks acceptance by the Indonesian foreign capital is relatively low compared to the developing countries in Asia. China is the largest recipient of foreign capital, followed by Singapore and Malaysia. In more remote Indonesian government continues its efforts to increase Foreign direct investment, especially from South Korea. As we all know South Korea is an important trading partner for Indonesia. Indonesia bilateral relations with South Korea have occurred since the New Order and has impacted the relatively low added value for Indonesia, especially in the 1990s. In the development of bilateral relations between the two countries increased, especially after entering the Reformation Era. This condition is supported by inflation in Indonesia is considered quite stable. This study aims to determine the effect of inflation on the acceptance Indonesia Foreign direct investment from South Korea to Indonesia during the period 2000-2014. The research methodology used is quantitative approach using simple regression model. Based on the results of the calculations, and a significant negative correlation between inflation in Indonesia and the acceptance of Direct Foreign Investment from South Korea in Indonesia. This is consistent with Fisher's theory that the decline in inflation Indonesia will be followed by a decline in interest rates Indonesia which ultimately impact the increased investment in Indonesia. Besides these reasons, the negative relationship, emphasizing that the investment climate in Indonesia has improved so trust Foreign investors, especially from South Korea in Indonesia is quite large.Â Keywords: Foreign direct investment, inflation in Indonesia